2020
DOI: 10.1155/2020/8887914
|View full text |Cite
|
Sign up to set email alerts
|

Aquifer Vulnerability: Its Protection and Management—A Case Study in Pangkalpinang City, Indonesia

Abstract: Increased anthropogenic activity in urban areas has exacerbated the vulnerability of groundwater resources. The AVI, GOD, SINTACS, and DRASTIC methods were used to analyze groundwater vulnerability in Pangkalpinang City. Schlumberger vertical electrical sounding was used to determine the lithology and aquifer configuration in the study area. There are three vulnerability index areas in the city of Pangkalpinang. Low levels of aquifer vulnerability were generally found in the southeastern and northwestern parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…Hasil tinjauan literatur sistematik menunjukkan ada beberapa metode yang digunakan dalam penelitian kerentanan airtanah di Indonesia diantarnaya GOD (Sukmawati Rukmana et al, 2020;Widodo et al, 2021), DRASTIC (Aribowo et al, 2021b;Kesuma et al, 2017;Koesuma et al, 2021;Machdar et al, 2018;Putranto & Aribowo, 2020;Wicaksono et al, 2013), HGZ (Klaas et al, 2017(Klaas et al, , 2018, COP (Yogafanny & Legono, 2021), APLIS (Syafarini et al, 2021), SVV (Aribowo et al, 2021a), EPIK (Riyanto et al, 2020;Syahidin & Murti, 2021), AVI Putranto & Yusrizal, 2018;Siswoyo & Azhar, 2019), SINTACS dan SINTACS Lu (Ayu Wandari et al, 2020;Primastuti & Kusratmoko, 2018), SI (Marjuanto et al, 2019) , DRANTHVP (Ahadiah & Widyastuti, 2020), PCSM (Putranto & Marjuanto, 2021). Selain satu metode tunggal ada juga yang menggunakan integrasi beberapa metode diantaranya GOD dan DRASTIC , AVI -GOD -SINTACS -DRASTIC (Nugraha et al, 2020)…”
Section: Hubungan Antar Kata Kunciunclassified
“…Hasil tinjauan literatur sistematik menunjukkan ada beberapa metode yang digunakan dalam penelitian kerentanan airtanah di Indonesia diantarnaya GOD (Sukmawati Rukmana et al, 2020;Widodo et al, 2021), DRASTIC (Aribowo et al, 2021b;Kesuma et al, 2017;Koesuma et al, 2021;Machdar et al, 2018;Putranto & Aribowo, 2020;Wicaksono et al, 2013), HGZ (Klaas et al, 2017(Klaas et al, , 2018, COP (Yogafanny & Legono, 2021), APLIS (Syafarini et al, 2021), SVV (Aribowo et al, 2021a), EPIK (Riyanto et al, 2020;Syahidin & Murti, 2021), AVI Putranto & Yusrizal, 2018;Siswoyo & Azhar, 2019), SINTACS dan SINTACS Lu (Ayu Wandari et al, 2020;Primastuti & Kusratmoko, 2018), SI (Marjuanto et al, 2019) , DRANTHVP (Ahadiah & Widyastuti, 2020), PCSM (Putranto & Marjuanto, 2021). Selain satu metode tunggal ada juga yang menggunakan integrasi beberapa metode diantaranya GOD dan DRASTIC , AVI -GOD -SINTACS -DRASTIC (Nugraha et al, 2020)…”
Section: Hubungan Antar Kata Kunciunclassified
“…Kujama like other parts of Nigeria, where rapid large agricultural practices are emerging, the contamination of water supplies due to the application of agrochemicals, and irrigation need to be properly addressed. While some remarkable studies argued that the extent of groundwater pollution is a measurement of the hydraulic conductivity value of the earth's subsurface [6,7,8,9], recent studies have also shown that the deposited agrochemicals, wastes, pesticides, oodplain on the land, undergo series of chemical reactions and changes, which in ltrate the shallow sediments above the water-bearing unit (water table) to contaminate the surface and subsurface water through leaching of leachates [10,11,12,13,14,15,16,17]. However, some researchers observed that the pollutants or the uvial contaminants released into an environment hardly remain at the surface level but usually discharge and penetrate the ground into the water-bearing unit [18,19].…”
Section: Introductionmentioning
confidence: 99%